RELATIONSHIP BETWEEN δ13C AND δ18O VALUES OF THE RECENT NAUTILUS AND BRACHIOPOD SHELLS IN THE WILD AND THE PROBLEM OF RECONSTRUCTION OF FOSSIL CEPHALOPOD HABITAT - Zakharov Y.D.; Smyshlyaeva O.P.; Popov A.M.; Ignatiev A.V.; Shigeta Y. (My University, 2006)
Ontogenetic change in δ18O values of the investigated Nautilus pompilius Linne shell in the Philippines (Tagnan, Panglao Islands, Bohol Island area) confirms data, in which Nautilus in the wild shows a marked increase in oxygen isotopic composition between embryonic and post-embryonic stages. The increase in δ18O in post-embryonic septa reflects a migration into colder, deeper (about 300 m) waters. Judging from the isotopic composition of aboral and adorai parts of the last septum, the amplitude of the short term vertical migration for the investigated sample seems to be about 70 m. Relative fluctuation in δ13C values for the living Nautilus, as well as living brachiopods, might be connected with annual cycles of the phytoplankton development. The negative δ13C excurse (-2.5‰) fixed in the septa 9 of the investigated Nautilus pompilius shell seems to be connected with a weakening of phytoplankton bioproductivity related to low solar activity. It is suggested that ammonoids, like living Nautilus spent the most part of their lives near the sea-floor but unlike Nautilus and late Cretaceous belemnites they did not experience, apparently, significant short-term vertical migration.
Keywords: AMMONOIDS; NAUTILUS; OXYGEN ISOTOPIC COMPOSITION; VERTICAL MIGRATION; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая